Home / Digital SAT Math : Equivalent expressions -Practice Questions

Digital SAT Math : Equivalent expressions -Practice Questions

SAT MAth Practice questions – all topics

  • Advanced Math Weightage: 35% Questions: 13-15
    • Equivalent expressions
    • Nonlinear equations in one variable and systems of equations in two variables
    • Nonlinear functions

SAT MAth and English  – full syllabus practice tests

  Question  Easy

$
T=N C
$

For a particular college program, the given equation re lates the cost of tuition \(T\), in dollars, to the number of credits taken, \(N\), and the cost of each credit \(C\), in dollars, where \(N\) and \(C\) are positive numbers. Which equation correctly expresses \(C\) in terms of \(N\) and \(T\) ?
A) \(C=T N\)
B) \(C=T-N\)
C) \(C=\frac{N}{T}\)
D) \(C=\frac{T}{N}\)

▶️Answer/Explanation

Ans: D

Given the equation:
\[ T = N C \]

We need to solve for \( C \) in terms of \( N \) and \( T \).

1. Start with the original equation:
\[ T = N C \]

2. To isolate \( C \), divide both sides by \( N \):
\[ C = \frac{T}{N} \]

So, the correct answer is:
\[ \boxed{D} \]

  Question   Easy

\(1210(x+120)=120\)
Which of the following equations has the same solution as the given equation?
A. \(x+120=12\)
B. \(x+120=130\)
c. \(x+12=12\)
D. \(x+12=120\)

▶️Answer/Explanation

Ans:A

To find an equation with the same solution as \(10(x+120) = 120\), we first need to solve the given equation for \(x\).

\[10(x+120) = 120\]

Divide both sides by \(10\):

\[x + 120 = 12\]

Subtract \(120\) from both sides:

\[x = 12 – 120\]

\[x = -108\]

Now, let’s check which of the given equations has the same solution:

A. \(x + 120 = 12\) -> \(x = -108\)
B. \(x + 120 = 130\) -> \(x = 10\)
C. \(x + 12 = 12\) -> \(x = 0\)
D. \(x + 12 = 120\) -> \(x = 108\)

Among these options, option A has the same solution as the given equation, \(x = -108\).

Therefore, the correct answer is option A: \(x + 120 = 12\).

 Question   Easy

\(2-x^{2}-x^{2}-2\)

Which of the following is equivalent to the given expression?

A. 0
B. 2
C. \(-x^{2}\)
D. \(-2x^{2}\)

▶️Answer/Explanation

Ans: D

 We’re given the expression \( 2 – x^2 – x^2 – 2 \), which simplifies to \( -2x^2 \). So, the equivalent expression is \( \text{D. } -2x^2 \).

Question Easy

Which expression is equivalent to \(x^4(3x^2 + 9x − 8)\) ?

A)\(x^4 + 3x^2 +9x − 8\)

B)\(3x^6 + 9x^5 − 8x^4\)

C)\(3x^8 + 9x^5 − 8x^4\)

D)\(12x^2 + 36x − 32\)

▶️Answer/Explanation

B)\(3x^6 + 9x^5 − 8x^4\)

We need to find the expression equivalent to \(x^4(3x^2 + 9x – 8)\).

Distribute \(x^4\) to each term inside the parentheses:
\[ x^4(3x^2) + x^4(9x) + x^4(-8) \]
\[ = 3x^6 + 9x^5 – 8x^4 \]

The correct expression is:
B) \(3x^6 + 9x^5 – 8x^4\).

 Questions  Easy

If x > 0, which of the following is equivalent to \(\frac{1}{x}+\frac{1}{2x}\)?

A. 1/x

B. 1/2x

C. 3/2x

D. 2/3x 

▶️Answer/Explanation

Ans: C

If \(x>0\), which of the following is equivalent to \(\frac{1}{x}+\frac{1}{2 x}\)?

To simplify \(\frac{1}{x}+\frac{1}{2 x}\), we find a common denominator:

\[\frac{1}{x}+\frac{1}{2x} = \frac{2}{2x} + \frac{1}{2x} = \frac{3}{2x}\]

So, the equivalent expression is C) \(\frac{3}{2x}\).

Scroll to Top